MATH SOLVE

2 months ago

Q:
# Given h(x) = (3x-4), f(x) = (7x+2), and g(x) = (9x+1), which of the following is equivalent to 2x+3?A. h(x) + g(x)B. g(x) + f(x)C. g(x) * h(x)D. h(x) - g(x)

Accepted Solution

A:

A) h(x)+g(x)=(3x-4)+(9x+1)=12x-3

B) g(x) + f(x)=(9x+1)+(7x+2)=16x+3

C) g(x)*h(x)= (9x+1)(3x-4)=27x²+3x-36x-4=27x²-33x-4

D)h(x)-g(x)=(3x-4)-(9x+1)= - 6x -5

if f(x)= -7x +2

B) g(x)+f(x)=(9x+1)+(-7x+2)=9x-7x+1+2=2x+3

answer B

B) g(x) + f(x)=(9x+1)+(7x+2)=16x+3

C) g(x)*h(x)= (9x+1)(3x-4)=27x²+3x-36x-4=27x²-33x-4

D)h(x)-g(x)=(3x-4)-(9x+1)= - 6x -5

if f(x)= -7x +2

B) g(x)+f(x)=(9x+1)+(-7x+2)=9x-7x+1+2=2x+3

answer B